Cytological findings by fine needle aspiration versus definitive biopsy in apparently bening solid breast nodules (Boletin Médico de Postgrado, 2020)
Breast nodules are one of the most common causes of medical consultation in women. A descriptive cross-sectional study was carried out in order to compare cytological findings by fine needle aspiration versus definitive biopsy in apparently benign solid breast nodules in 31 patients who attended the Servicio de Cirugía Ambulatoria of the Hospital Central Universitario Dr. Antonio Maria Pineda and a private clinic. The highest nodule prevalence was observed in the 21-30 years old group (35.48%) being sonographically BIRADS 3 in 66.67% of cases; by mammography, BIRADS 3 and BIRADS 4a was only present in 11.11% of cases, respectively. The most common lesion by fine needle aspiration was fibroadenoma (69.44%). The most common lesion by biopsy was fibroadenoma (88.88%) and fibrocystic condition and benign phyllodes tumor in 5.56% of cases, respectively. There was a 100% agreement between cytological findings obtained by fine needle aspiration and histological results obtained by biopsy.
Keywords: breast nodule; fine needle aspiration; biopsy; fibroadenoma; cytology